2015
DOI: 10.3923/ajpsaj.2015.179.190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selection for Weight of Early Eggs on Egg Production Traits in Japanese Quail

Abstract: The present study aimed to measure the direct response of selection for high egg weight of the first 10 eggs laid at the beginning of egg production period in Japanese quail through three generations of selection. The egg weight of the first 10 eggs (EW 10 ) as direct response increased in the selected line when compared with control line from 10.43 g in the base generation to 12.52 g in the second generation after selection with rate of 0.69 g per generation. The Age at Sexual Maturity (ASM) trait increased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Our findings agree with those reported for AFE 4,32,36,45 . However, a different trend reported by Bahie El-Deen et al 46 who showed that the overall means of AFE were 52.61 and 50.45 d for control and selected lines in Japanese quail.…”
Section: Resultsmentioning
confidence: 69%
“…Our findings agree with those reported for AFE 4,32,36,45 . However, a different trend reported by Bahie El-Deen et al 46 who showed that the overall means of AFE were 52.61 and 50.45 d for control and selected lines in Japanese quail.…”
Section: Resultsmentioning
confidence: 69%
“…Significant generation effects for body weight as well as egg production traits were also observed by Mahmoud et al (2014). Significant (P<0.05) differences in egg weight and birth weight through generations has been reported by El-Deen et al, 2015. As per Taskin et al (2017 body weight through different generations varied significantly (P<0.01) barring the parental generations.…”
Section: Effect Of Season Of Hatch/generationmentioning
confidence: 57%
“…The current study supports the findings of Alkan et al (2010) , who discovered a significant difference in egg weight for both lines chosen for higher body weight and egg production in Japanese quails. El-Deen et al (2015) also reported increased egg weight after two generations of selection for higher egg production compared to the control line.…”
Section: Discussionmentioning
confidence: 91%